Fibrosis in connective tissue disease: the role of the myofibroblast and fibroblast-epithelial cell interactions - Krieg, Thomas (BioMed Central|1, 2007)
Fibrosis, characterized by excessive extracellular matrix accumulation, is a common feature of many connective tissue diseases, notably scleroderma (systemic sclerosis). Experimental studies suggest that a complex network of intercellular interactions involving endothelial cells, epithelial cells, fibroblasts and immune cells, using an array of molecular mediators, drives the pathogenic events that lead to fibrosis. Transforming growth factor-β and endothelin-1, which are part of a cytokine hierarchy with connective tissue growth factor, are key mediators of fibrogenesis and are primarily responsible for the differentiation of fibroblasts toward a myofibroblast phenotype. The tight skin mouse (Tsk-1) model of cutaneous fibrosis suggests that numerous other genes may also be important.